The Role Of The Concept Of Fractions In The Development Of Primary School Pupils’ Mathematical Thinking - Jalilov Muhammadali Abdumutalibovich; Nomonova Durdonaxon (European International Journal of Pedagogics, 2026)
This study examined the role of the concept of fractions in the development of primary school pupils’ thinking. In the course of the research, the impact of learning fractions on key components of thinking—students’ logical reasoning skills, as well as their abilities in analytical and synthetic thinking—was analyzed. Through an experimental approach, the level of pupils’ mastery of fractions, the effectiveness of solving logical tasks, and indicators of growth in overall mathematical thinking were determined. The results show that working with the concept of fractions in primary grades significantly enhances pupils’ thinking abilities.